Assessment programs of the High Performance Gym after the state of emergency - Approaches to return to strength and conditioning session for high-performance athletes at the Japan High Performance Sport Center II - Suzuki, E.; Nakamoto, S.; Azuma, Y.; Yamashita, D. (Journal of High Performance Sport, 2021)
The Japan High Performance Sport Center (JHPSC) has been taking an integrated approach by combining Olympic and Paralympic sports in order to strengthen international competitiveness in Japan. Since 2013, we have been operating the High Performance Gym (HPG), which is equipped with a state-of-art training facility at the JHPSC. Our mission is to offer effective, individualized training programs for athletes through assessing their functional abilities. Our main assessment programs consist of postural, aerobic and/or anaerobic, and strength and/or power assessments. Due to the COVID-19 pandemic, almost all athletes were inactive and unable to train normally. In Japan, there was a state of emergency, from April to May 2020, and as a result all training facilities at the JHPSC were closed. To support the athletes' return to training, the HPG has implemented specialized and customized fitness assessments in accordance with COVID-19 guidelines. These assessments have been vital to help athletes prepare for the Olympics and Paralympics by improving their performance.